ANALISIS CURRENT RATIO DAN NET PROFIT MARGIN TERHADAP HARGA SAHAM PADA PERUSAHAAN JASA GROSIR DI BEI - Novaliana, Ika; Dekrijanti, Indra; Mahendra, Prasetya Tri; Kinasih, Aprilia Wulan (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2023)
This study aims to determine the effect of the current ratio and net profit margin on stock prices carried out by large trading sub-sector service companies (wholesalers) listed on the Indonesia Stock Exchange. The population of this study is large trade (wholesale) sub-sector service companies listed on the IDX in 2021-2022. Forty companies were determined as samples based on the purposive sampling method. This quantitative study used secondary data and multiple regression analysis to analyze the data. The results of this study revealed the current ratio has a negative and significant effect on stock price and net profit margin has a positive and significant effect on stock price. Current ratio and net profit margin simultaneously affect stock price. The current ratio negatively affects stock price, while net profit margin positively affects stock price.